Imagism of Chinese Poem: A Literary Study on Ezra Pound’s Poetry - Zixi Li (Universitas Pasundan, 2022)
Imagism aims at creating poetry as art, pursuing the clarity and beauty of language, and implying personal emotions via images. While Imagism brings the most influential change in English literature, Chinese traditional poetry with its unique cultural and historical-style stands out in world literature with rich emotional expression through images. This literary study compares Ezra Pound’s imagist poems with classical Chinese poetry, reviewing his translations of Chinese. To scrutinize the data, a qualitative research method that covers document analysis techniques was implemented comprehensively. The research reveals that Pound’s translated Chinese poems build a strong bond between the two cultures. Chinese traditional poems and Imagism poems share their love of descriptive language, a passion for accurate detail creation, joyfulness towards metaphor, analogy, personification, and other writing techniques, while they all conserve their own art form and identities